Study of Chemical and Biological Aspects of Valeriana wallichii DC. Root Essential Oil - Parveen, Zahida; Siddique, Saima; Shafique, Muafia; Jabeen Khan, Shaista; Khanum, Razia (Asian Journal of Chemistry, 2012)
The essential oil of Valeriana wallichii DC. root, which is an indigenous plant was extracted by hydro distillation. Chemical composition of the oil by GC-MS analysis revealed the presence of seven new components i.e. isoaromadendrene epoxide (3.435 %), isocaryophyllene (1.919 %), epiglobulol (1.692 %), longifolene-[V4] (1.618 %), panasinene (1.452 %), lognifolenaldehyde (0.875 %) and butanoic acid, 3-methyl-, 3-methylebutylster (0.840 %). Patchouli alcohol (16.425 %) was found to be the major component among ten identified components of the essential oil. Antibacterial activity and antioxidant activity of the said essential oil was investigated for the first time. The antibacterial potential of the essential oil of V. wallichii was determined by paper disc diffusion method, against Gram positive and Gram negative bacteria. Essential oil without any dilution was found to be more effective against all test microbes as compared to the standard antibiotics i.e. streptomycin and penicillin G. used as positive controls. DPPH scavenging effect was 96.47 % for essential oil of V. wallichii. Antioxidant activity of the oil was 11.27 % higher than BHT used as control.